Development of Social Studies Multimedia Learning Based on Discovery Learning Using Kodular at The Junior High School Level - Lasmaria Samosir; Erma Yulia; Sahat Siagian; Sahat Maringan Samosir (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This study aims to develop interactive learning multimedia based on the Discovery Learning approach using the Kodular application for teaching Demand, Supply, and Equilibrium Price in Economics subjects at SMP Swasta Santo Thomas 1 Medan. The research adopts a Research and Development (R&D) approach, utilizing the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), which is commonly used in educational product development. The development process was carried out systematically through five stages, focusing on creating multimedia that supports student self-directed learning and enhances their understanding of the subject matter. The results of the study show that the developed multimedia was well received by students, as evidenced by its effectiveness in facilitating active learning and increasing student engagement. This is reflected in the significant improvement in the average student scores from 39.28 before the implementation to 94.53 after the use of Kodular-based multimedia. At the evaluation stage, the application was well accepted and provided a deeper understanding of economic concepts to the students, based on positive feedback from expert validators and learners. The study concludes that the implementation of Discovery Learning through Kodular significantly enhances the quality of instruction, providing students with a deeper comprehension of complex topics in Economics.